SISTEM MONITORING NIRKABEL VOLUME CAIRAN INFUS PASIEN MENGGUNAKAN MIKROKONTROLER ATMEGA328 - Ramadhan, Febriyansyah; Wahyudi, Ricky (INFOTECH journal, 2023)
The hospital is a health facility that provides diagnostic and therapeutic services to patients for various diseases and mental health problems, both surgical and non-surgical. It is a place to get healing for an illness that is suffered. At present medical devices need attention to get the right results when treating patients, of course, increasing technological sophistication. One of the common medical procedures performed on patients is to administer drugs via intravenous injection. Intravenous injection or infusion is done by inserting fluids into a vein through a needle to replace fluids or nutrients that are lost from the body. However, because the number of patients is large and each patient may require a different infusion, the nurse must check each infusion individually in each room. To overcome this problem, a tool was created that can automatically monitor the volume of infusion fluids in each patient room, so that nurses can monitor patient infusions from one place and reduce the need to check manually. The research method used is to manufacture the tool and then conduct an experiment, namely testing the tool and analyzing the results of the tool test.